Сторічний ювілей фундатора української лісівничої науки – професора П. С. Пастернака - Tkach, V. P.; Voron, V. P. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2025)
This manuscript commemorates the centenary of the birth of Professor Petro S. Pasternak, an Honored Forester of Ukraine and an outstanding Ukrainian scientist. Through his original scientific ideas, profound knowledge, and influential publications, he made a substantial contribution to forestry and silviculture, forest soil science, forest typology, protective afforestation, and forest ecology. His analytical thinking, broad erudition, logical and precise scientific reasoning, and clarity of presentation distinguished him as an exceptional scholar. Owing to his innate intelligence, leadership qualities, remarkable memory, diligence, ability to engage in scientific debates and defend his views, and personal integrity, Professor Pasternak earned deep respect among colleagues, students, and collaborators. Professor Petro Pasternak was born on 23 February 1925 in the town of Skvyra, Kyiv region. In September 1942, he volunteered for military service and took part in combat operations. After demobilization in 1946, he entered the Kyiv Forestry Institute, graduated in 1950, and subsequently pursued postgraduate studies at the Forest Institute of the Ukrainian Academy of Sciences. In December 1953, Petro Pasternak defended his PhD thesis entitled “The Impact of Caragana on Forest Soil Fertility” and continued his career at the Forest Institute as a junior and later senior researcher. From 1953 onwards, his research focused on forest regeneration in the Ukrainian Carpathians and on increasing forest productivity and resilience. In 1956, he was appointed Director of the Transcarpathian Forest Research Station of the Ukrainian Research Institute of Forestry and Forest Melioration (URIFFM). In 1964, he became the first Director of the Carpathian Branch of URIFFM in Ivano-Frankivsk. There, he initiated research into the causes of catastrophic windstorms and windbreaks, as well as the biological cycles of matter in forest ecosystems. A central component of his work was a comprehensive study of the relationships between forest types and soil formation, leading to the classification of morphological and physicochemical soil properties in relation to forest types. In August 1968, Petro Pasternak was appointed Director of URIFFM. To address emerging environmental challenges, he established the first forest ecology laboratory in Ukraine, which investigated the impacts of air pollution, uncontrolled recreation, and other anthropogenic pressures on forest health and water resources, and developed measures to prevent or mitigate their adverse effects. From the earliest days following the Chernobyl nuclear accident, research programs under his leadership were launched to address a wide range of problems in radioactively contaminated regions of Ukraine. These studies assessed radionuclide distribution and migration pathways in forest ecosystems and provided recommendations for forest management under radioactive contamination. Professor Pasternak was the first in Ukraine to initiate forest monitoring as a distinct scientific discipline. He founded a scientific school of forest ecologists; under his supervision, more than 30 researchers defended their dissertations and later became leading scientists in forestry and related fields. His scientific interests encompassed a wide range of theoretical and applied issues, including interactions among tree species in different forest types, forest vegetation and forestry zoning, forest management based on zonal-typological and program-targeted principles, sustainable forest use and ecosystem protection under anthropogenic pressure, and the establishment of agroforestry and reclamation plantations, particularly on former agricultural lands. 4 Figs., 17 Refs.